Grammatical Gender in American Norwegian Heritage Language: Stability or Attrition? - Lohndal, Terje; Westergaard, Marit (Frontiers in Psychology, 2016)
This paper investigates possible attrition/change in the gender system of Norwegian heritage language spoken in America. Based on data from 50 speakers in the Corpus of American Norwegian Speech (CANS), we show that the three-gender system is to some extent retained, although considerable overgeneralization of the masculine (the most frequent gender) is attested. This affects both feminine and neuter gender forms, while declension class markers such as the definite suffix remain unaffected. We argue that the gender category is vulnerable due to the lack of transparency of gender assignment in Norwegian. Furthermore, unlike incomplete acquisition, which may result in a somewhat different or reduced gender system, attrition is more likely to lead to general erosion, eventually leading to complete loss of gender.